Kompos Pelet: Solusi Praktis Berkelanjutan, dan Berbasis Ekonomi Sirkular dalam Pengelolaan Sampah Rumah Tangga - Rosariastuti, MMA Retno; Sutami, Sutami; Dewi, Widyatmani Sih; Sudadi, Sudadi (PRIMA: Journal of Community Empowering and Services, 2026)
Pellet Compost: A Practical, Sustainable, and Circular Economy-Based Solution for Household Waste Management. One type of waste that is readily available is leaf litter. Leaf litter is a major contributor to household waste. Compostable waste has great potential to be utilized optimally to provide both economic and ecological benefits. This community service program was carried out from July to November 2025 through several stages: preparation, implementation, and evaluation. The purpose of this activity is to process organic waste into environmentally friendly pellet-based compost. Pellet-based compost is a solid organic fertilizer formed into pellets. Its shelf life is longer than loose compost. Pellet compost is drier, more visually appealing, richer in nutrients, and has a higher market value. The ingredient ratio in pellet production is a key factor that determines the quality, efficiency, and final performance of the pellets. The best ingredient ratio for pellet production between compos: tapioca flour: coconut shell charcoal: and water is 10:1:1:2. The sale of coconut shell charcoal pellets yields higher profits compared to bran and dolomite, amounting to Rp. 2,478 per piece. This approach offers a practical and sustainable solution, providing ecological benefits by reducing organic waste and supporting a circular economy in waste management. This community service initiative is expected to help the community understand how to produce pellet compost, enabling them to meet agricultural needs independently without relying on external raw materials. The program demonstrates that solving environmental issues can go hand in hand with improving the regional economy. This reflects the essence of Sustainable Development Goal (SDG) 12, which is responsible consumption and production.